Antifungal activity of Rosmarinus officinalis Linn. essential oil against Candida albicans, Candida dubliniensis, Candida parapsilosis and Candida krusei - Gauch, Lurdete Maria Rocha (2014)
The antifungal and anti-germ tube formation activity of Rosmarinus officinalis Linn. essential oil was tested against four Candida strains (C. albicans, C. dubliniensis, C. parapsilosis and C. krusei). Inhibition halo sizes and minimal inhibitory concentrations (MIC) were obtained using radial diffusion and micro dilution tests, respectively. The minimal fungicidal concentration (MFC) was obtained from the MIC assay. Additionally, the effect of the essential oil on germ tube formation in C. albicans and C. dubliniensis was evaluated. The MIC50 ranged from 0.5% to 2%, while the MFC ranged from 1% to 2%. We observed total inhibition of germ tube formation in C. albicans and C. dubliniensis. The R. officinalis Linn. essential oil displayed powerful inhibitory and fungicidal activity against specific Candida strains.